Surgical Obturator as an Immediate Prosthesis Post Hemimaxillectomy of Palatal Squamous Cell Carcinoma: A Case Report - Ratri Maya Sitalaksmi, - (JIOH (Wolters Kluwer Medknow Publications), 2022)
Surgical management of oral squamous cell carcinoma results in significant defects in the oral and maxillofacial regions. This case study aims to support the formation of an intraoral defect profile, shorten recovery time, and improve the patient’s psychological aspects by inserting a postoperative surgical obturator. A 44-years-old male presented to Dental Hospital Universitas Airlangga at the referral from General Hospital Dr. Soetomo Head and Neck Surgery Department due to recurrent palatal squamous cell carcinoma. The patient required a surgical obturator to restore anatomical defect post-hemimaxillectomy. Multidiscipline discussion forums were performed to determine the plan for tissue removal, and the prosthodontist designed the surgical obturator. The design was made utilizing the retention of the remaining 17 and 27 teeth with Adams claps. In this case, mechanical retention was achieved by a wire, which was attached to the zygoma bone. The artificial teeth were arranged in the anterior area to improve aesthetic, while in the posterior region, the artificial teeth were not used to minimize the masticatory loading. Surgical obturator improved the masticatory function and psychology of the patient.